Oil- and Gas-Rich Azerbaijan’s Economic Diversification: Analysis of Global Experiences and Prospects for Application - Jabbarova, Aynur; Ashurbayli-Huseynova, Nigar; Akbarova, Sevda; Orucova, Mehpare; Celik, Levent (International Journal of Energy Economics and Policy, 2026)
This paper examines the current state and future prospects of economic diversification policy in Azerbaijan’s economy, which remains highly dependent on oil and gas resources. Based on time-series data covering the period 2014–2024, trend analysis was conducted to visualize structural changes and identify intersectoral dynamics. Using ARDL (Autoregressive Distributed Lag) and VAR (Vector Autoregression) models, the short- and long-term interactions between the share of oil in GDP, non-oil exports, innovation and research expenditures, and fiscal revenues were empirically assessed. The findings indicate that the share of the oil sector in GDP decreased from 41% to 27.5%, while non-oil exports and R&D expenditures demonstrated upward trends. However, the high share of oil revenues in the state budget persists, confirming that sustainable diversification within the fiscal structure has yet to be fully achieved. Strategic investments by SOCAR and other energy enterprises in non-oil sectors play a crucial role in this transition process, providing additional impetus to industrial transformation. A comparative analysis with Norway, the United Arab Emirates, and Kazakhstan, based on panel data, revealed the potential for local adaptation of international experiences in this area. Applying SWOT and GAP analysis approaches, Azerbaijan’s economic strengths and weaknesses were systematized, leading to the conclusion that institutional reform is necessary within the framework of strategic planning. The main conclusion of the paper is that Azerbaijan, in the course of its transition to the post-oil stage, must strengthen its innovation policy and improve institutional mechanisms aimed at developing non-oil sectors.